Acute Rotavirus gastroenteritis among children - Saeed, Ali Y. (Sulaimani Journal for Pure and Applied Sciences, 2000)
Stool samples were collected from two hundred children in both sexes under two years of age admitted to the pediatric word of Azadi Hospital suffering from acute gastroenteritis during winter months of 1999. These stool samples were investigated by Rota- kit agglutination test Rotavirus was detected in 60 (30.0%) of children and was all most frequently diagnosed in age group 1-6 months (38. 3%), but being considerably decreased with the age increases over one year. There was no statistical significant difference between boys and girls rotavirus infection. The pH of the stool samples in the majority of cases was acidic with absence of RBA' and pus cells on direct microscopic examination.